Hubungan Tingkat Sosial Ekonomi Keluarga terhadap Tingkat Motivasi Belajar Peserta Didik pada Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Kelas X di SMA Negeri 1 Menganti - Fahmi Husnul Adib; Andhega Wijaya (Journal on Education, 2024)
Motivation to learn is an effort that can have side effects on students and to move and carry out learning activities in order to achieve their goals and also get satisfaction from those activities. This research aims to determine the influence of family socio-economic level on the level of learning motivation in class X PJOK learning at SMA Negeri 1 Menganti. The population of this research was class X students at SMA Negeri 1 Menganti, totaling 380 students. Using quantitative correlational methods using simple regression analysis techniques. There are two instruments used, namely the Family Socioeconomic scale and Learning Motivation. The results of the research show that there is an influence of family socio-economic level on the level of learning motivation in class X PJOK learning at SMA Negeri 1 Menganti with a value of Sig. 0.000 < 0.05. The family's socio-economic contribution to learning motivation is 46.1%.